The Politics of Transformative Nationality: An Experience of Moslem Theologian (Ulama) at Indonesian Islamic Boarding Schools - Nurul Huda (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
The communities of Islamic boarding schools as institutions that are born from the basis and doctrine of Islam are meticulously and courageously successful in dialectics with the facts of life. In the colonial era, the communities of Islamic boarding schools did not only fight because of the reasons which the colonialism exploited and treated the people in a non-human way, but also more than the religious doctrine was the most basic foundation so that resistance occurred continuously. The communities of Islamic boarding school is also able to provide a theological solution to critical issues related to the basic foundation of nation and state, such as the basic state debate in the Jakarta charter, and the single principle of Pancasila. As the result, the communities of Islamic boarding schools have made a final decision known the Unitary State of the Republic of Indonesia (NKRI), Bhinneka Tunggal Eka (unity in diversity), Pancasila and the 1945 Constitution is the final and complete for Indonesian nation.